Use of the otolith shape analysis in stock identification of anglerfish (Lophius piscatorius) in the Northeast Atlantic - Cañás, Lucía; Stransky, Christoph; Schlickeisen, C.; Sampedro-Pastor, Paz; Fariña-Pérez, Celso (2012)
Sí